Sosialisasi Untuk Menumbuhkan Kesadaran Masyarakat Tentang Manfaat Lubang Resapan Biopori Dalam Meningkatkan Kesejahteraan Ekonomi Masyarakatdi Desa Mrisi Kecamatan Tanggung Harjo Kabupaten Grobogan - Harini, Harini; Yuliyani, Dwi Nur; Marliyah, Lili; Haksasi, Banun Sri; Aulia, Hidayatul (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2024)
This study's overarching goal is to disseminate information about the environmental preservation and economic benefits of biopore absorption holes in Mrisi Village, Guberharjo District, Grobogan Regency via education and training in the Biopori Absorption Hole Technique. When it comes to minimizing waterlogging, enhancing soil quality, and increasing groundwater availability, biopore infiltration pores are invaluable. They also help with flooding concerns. The general population, however, is still in the dark about these advantages. So, the goal of the outreach effort was to get more people to know about biopori technology and to help put it to use. Direct counseling, instruction, and aid in making and maintaining biopore absorption pores are some of the ways that socialization is accomplished. We hope that by raising people's awareness of biopore absorption holes and how important they are for environmental protection, we may encourage better management of our natural resources and, in turn, boost people's economic well-being. As an added bonus, the village's economy has a better chance of being sustainable because to the biopore absorption pores, which should boost agricultural production and water availability. Keywords : Raising Public Awareness, Biopore Infiltration Holes, and Economic Welfare